Evaluating 4 years of Jokowi Sea Toll Policy: The concept of Indonesia-Centric connectivity for economic equality - Kurniawati Sa'adah; Probo Darono Yakti; Siti R. Susanto (Faculty of Social and Political Science, Universitas Airlangga, 2019)
Indonesia categorised as a middle economy country according to the global economic standard. The government launched the World Maritime Fulcrum as a grand strategy or doctrine that alters the development paradigm from land-based to maritime-based. This paper will discuss the policies on which the Joko Widodo (Jokowi) Sea Toll Road as connectivity with the T3P (frontier, outermost, and remote) area can support the price disparity as a form of social justice. It was reviewed using connectivity, the political economy, and economic growth theory. The author used a qualitative method to analyse the problem in addition to paper-based research. In the beginning, the background of the Sea Toll policy will be discussed, alongside the presentation of the research questions and thesis responses. At the same time, the study will include how previous studies have looked at this issue. Only then will it move on to the next chapter, which discusses conceptual connectivity, political economy and economic growth. Furthermore, the policy development from the Archipelago Belt and Nusantara Pendulum through to the Sea Toll Road will be discussed. Massive budgetary costs and empty returning freight costs will be discussed as well. After that, we will discuss the sea highway route and then the evaluation. From this arrangement, it was finally resulted and concluded that the Sea Toll has been on the right path to reach its goal, which removed price disparities involving many records being continually updated by the government and all stakeholders including those in the business world. The importance of our research is how to discuss the Sea Toll over the past four years and how to request assistance and efficiency within this concept realise social justice. Thus, it can be put out as a reference for reviewers in the field of maritime and logistics.